Effects of Ginkgo leaf tablets on the pharmacokinetics of losartan and its metabolite EXP3174 in rats and its mechanism. (1st January 2018) - Dong, Baiping; Yuan, Suowei; Hu, Jinsheng; Yan, Yanzhen
Abstract: Context: Ginkgo leaf tablets (GLTs) and losartan are often simultaneously used for the treatment of hypertension in Chinese clinics. However, the herb–drug interaction between GLT and losartan is still unknown. Objective: This study investigates the effects of GLT on the pharmacokinetics of losartan and its metabolite EXP3174 in rats and its potential mechanism. Materials and methods: The pharmacokinetic profiles of losartan and EXP3174 of orally administered losartan (10 mg/kg) with or without GLT pretreatment (80 mg/kg/day for 10 days) in Sprague–Dawley rats were determined. In vitro, the effects of GLT on the metabolic stability of losartan were investigated with rat liver microsomes. Results: The C max (1.22 ± 0.25 vs 1.85 ± 0.37 μg/mL) and the AUC (0– t ) (6.99 ± 1.05 vs 11.94 ± 1.79 mg·h/L) of losartan increased significantly ( p < 0.05) with GLT pretreatment, while the C max (1.05 ± 0.19 vs 0.72 ± 0.12 μg/mL) of EXP3174 decreased significantly ( p < 0.05) compared to the control. The t 1/2 of losartan was prolonged significantly from 3.94 ± 0.62 to 4.75 ± 0.52 h ( p < 0.05). The metabolic stability of losartan was increased from 37.4 min to 59.6 min with GLT pretreatment. Discussion and conclusions: The results indicate that GLT might increase the plasma concentration of losartan and decrease the concentration of EXP3174 through inhibiting the metabolism of losartan.